We All Begin in a Little Magazine : and the Promise of Canada's Poets 1978-1998 (MQUP, 1998)
When Arc began publishing in 1978, it had one aim: to publish the best work by Canada's new and established poets. Celebrating Arc's first two decades, We All Begin in a Little Magazine testifies to how fully the editors realized their aspirations. It provides a rich cross section of Canada's poetry of the time, the most vital years thus far in the history of Canadian Literature. Read the work of your favourite poets just as they first made names for themselves. Rediscover the excitment you felt when you came across their poems in Arc Canada's best "little magazine."